Tidal Volume-Dependent Activation of the Renin-Angiotensin System in Experimental Ventilator-Induced Lung Injury - Mao, Xinjun; Krenn, Katharina; Tripp, Thomas; Tretter, Verena; Reindl-Schwaighofer, Roman; Kraft, Felix; Podesser, Bruno K; Zhu, Yi; Poglitsch, Marko; Domenig, Oliver; Abraham, Dietmar; Ullrich, Roman (Critical care medicine, 2022)
Ventilator-induced lung injury (VILI) is a major contributor to morbidity and mortality in critically ill patients. Mechanical damage to the lungs is potentially aggravated by the activation of the renin-angiotensin system (RAS). This article describes RAS activation profiles in VILI and discusses the effects of angiotensin (Ang) 1-7 supplementation or angiotensin-converting enzyme (ACE) inhibition with captopril as protective strategies. Animal study. University research laboratory. C57BL/6 mice. Anesthetized mice (n = 12-18 per group) were mechanically ventilated with low tidal volume (LVT, 6 mL/kg), high tidal volume (HVT, 15 mL/kg), or very high tidal volume (VHVT, 30 mL/kg) for 4 hours, or killed after 3 minutes (sham). Additional VHVT groups received infusions of 60 μg/kg/hr Ang 1-7 or a single dose of 100 mg/kg captopril. VILI was characterized by increased bronchoalveolar lavage fluid levels of interleukin (IL)-6, keratinocyte-derived cytokine, and macrophage inflammatory protein-2 (MIP2). The Ang metabolites in plasma measured with liquid chromatography tandem mass spectrometry showed a strong activation of the classical (Ang I, Ang II) and alternative RAS (Ang 1-7, Ang 1-5), with highest concentrations found in the HVT group. Although the lung-tissue ACE messenger RNA expression was unchanged, its protein expression showed a dose-dependent increase under mechanical ventilation. The ACE2 messenger RNA expression decreased in all ventilated groups, whereas ACE2 protein levels remained unchanged. Both captopril and Ang 1-7 led to markedly increased Ang 1-7 plasma levels, decreased Ang II levels, and ACE activity (Ang II/Ang I ratio), and effectively prevented VILI. VILI is accompanied by a strong activation of the RAS. Based on circulating Ang metabolite levels and tissue expression of RAS enzymes, classical ACE-dependent and alternative RAS cascades were activated in the HVT group, whereas classical RAS activation prevailed with VHVT ventilation. Ang 1-7 or captopril protected from VILI primarily by modifying the systemic RAS profile.